Pelatihan Penyusunan Alat Evaluasi Non Tes bagi Guru Madrasah di Mataram - Herianto, Edy; Ismail, Mohammad; Dahlan, Dahlan; Basariah, Basariah; Tripayana, I Nengah Agus (Universitas Nusantara PGRI Kediri, 2021)
Evaluation of the learning process (through non-test) is often ignored by madrasah teachers in Mataram, at least getting less attention than learning outcomes (tests) as it is known that education is oriented to results and the process. Evaluation of learning outcomes and learning processes must be carried out in a balanced and simultaneous manner. Non-test evaluation tools are an essential part that must be considered by teachers, in addition, to test evaluation tools. If the teacher does not develop a non-test evaluation, it will impact the acquisition of student learning outcomes that do not describe the actual ability of a subject. Based on this consideration, training in the preparation of non-test evaluation tools is urgently needed so that teachers can carry out comprehensive evaluations using test and non-test tools. This service activity is in the form of training in preparing non-test evaluation tools in the madrasa environment. The method of implementing this activity follows the stages of preparation, observation of partner madrasas, training in the preparation of non-test evaluation tools, and follow-up. The activity results indicate that all stages of the activity went well and produced the product as determined. In addition, there has been an increase in participants' understanding and skills in preparing non-test evaluation instruments. It is evidenced by the average posttest score (75.00) is better than the pretest (32.12). This positive change is the answer to teacher problems in developing learning evaluations in madrasas.